Sport Public Relations Sponsorship: Manchester United Fans’ Emotional Engagement in Adidas–Stone Roses Collaboration - Fadilah, Alya Najla; Hidayat, Dasrun (Universitas Muhammadiyah Yogyakarta, 2025)
This research examines the collaboration between Manchester United, Adidas, and The Stone Roses as a sponsorship strategy that integrates football, music, and fashion using a qualitative phenomenological approach. Data were collected through in-depth interviews with 7 Manchester United fans. The researcher employed a Sport Public Relations approach to analyse the sponsorship collaboration's effect on emotional engagement and club identity. The research findings indicate that although this collaboration does not directly influence the core loyalty of fans, it reinforces pride and emotional connection with the club. Digital media plays a crucial role in expanding the reach of the campaign and enhancing fan interaction. This finding also provides insights for local football clubs to implement similar strategies by adjusting for cultural factors and the purchasing power of their fans. In conclusion, sponsorship in football serves not only as funding but also as a strategic tool in building club identity and enhancing fan engagement. The integration of cultural elements in sponsorship has been shown to increase the club's appeal and create long-term relationships between the club, sponsors, and its fan community.